YOUTH AND THE INTERNET: USEFUL ENGAGEMENT OR ADDICTION? (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article provides a comprehensive analysis of young people's internet usage in the modern digital era. It explores both the benefits—such as the internet’s role in education, communication, and access to information—and the increasing problem of internet addiction among youth. The study highlights the psychological, social, and health-related negative consequences of excessive internet use and offers suggestions for developing responsible and controlled internet habits. It also emphasizes the importance of motivating young people to seek inspiration from real life rather than the virtual world.